Flexible polymer-based triboelectric nanogenerator using Poly(vinylidene fluoride) and bombyx mori silk. (December 2022) - Sarkar, L.; Kandala, A.B.; Bonam, S.; Mohanty, S.; Singh, S.G.; Krishna Vanjari, S.R.
Abstract: This paper demonstrates a flexible triboelectric nanogenerator (TENG) using Poly(vinylidene fluoride) (PVDF) and silk by exploiting their inherent susceptibility for gaining and losing electrons. Bombyx mori silk possesses a strong capability of losing electrons whereas PVDF has the penchant for gaining electrons. Hence the combination of silk and PVDF could be explored as a novel and unique triboelectric pair for the fabrication of triboelectric nanogenerator. With this motivation, silk-PVDF-based TENG was fabricated on flexible substrate along with the systematic evaluation of its output performance. The primary objective of this paper is divided into two major parts. Initially, a comprehensive study was carried out to investigate the maximum output voltage of the TENG and its correlation with the morphology and composition of PVDF films. The structural optimization of the TENG was also performed in order to deduce the maximum output. Finally, various practical applications of silk-PVDF-based TENG were demonstrated. Through proper optimization, the maximum short circuit current and open circuit voltage acquired from the TENG was experimentally found out to be 11.3 μA and 611 V (peak to peak value), respectively. A relatively high output power density of 1.85 W/m 2 was obtained from the optimized nanogenerator for a load resistance of 10 MΩ. The efficacy of this prototype was investigated by powering up commercial red LEDs, charging of capacitors, and harvesting energy from human body movement. The TENG is not only capable to light up 56 commercial red LED bulbs but also is able to harvest mechanical energy from body motion. The highest amount of energy was scavenged from human footsteps.